2015
DOI: 10.3390/ijms160614143
|View full text |Cite
|
Sign up to set email alerts
|

Local Controlled Release of Polyphenol Conjugated with Gelatin Facilitates Bone Formation

Abstract: Catechins are extensively used in health care treatments. Nevertheless, there is scarce information about the feasibility of local administration with polyphenols for bone regeneration therapy, possibly due to lack of effective delivery systems. Here we demonstrated that the epigallocatechin-3-gallate-conjugated gelatin (EGCG/Gel) prepared by an aqueous chemical synthesis using 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-morpholinium chloride (DMT-MM) gradually disintegrated with time and facilitated bone formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…In another study, EGCG-gelatin conjugate is prepared by using 4-(4,6-dimethoxy-1,3,5-triazin-2yl)-4-methyl-morpholinium chloride and N-methylmorpholine as the cross-linking reagents in aqueous solution. 45 Recently, Fu et al 25 use 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as the coupling reagents to conjugate the carboxyl groups of chlorogenic acid with the amino groups of gelatin ( Fig. 3B).…”
Section: Chemical Coupling Methodsmentioning
confidence: 99%
“…In another study, EGCG-gelatin conjugate is prepared by using 4-(4,6-dimethoxy-1,3,5-triazin-2yl)-4-methyl-morpholinium chloride and N-methylmorpholine as the cross-linking reagents in aqueous solution. 45 Recently, Fu et al 25 use 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as the coupling reagents to conjugate the carboxyl groups of chlorogenic acid with the amino groups of gelatin ( Fig. 3B).…”
Section: Chemical Coupling Methodsmentioning
confidence: 99%
“…[35] Several studies conducted in vitro and in animal models have assessed the beneficial role of olive oil phenols on the formation and maintenance of bone through its modulation of both bone cell differentiation and function. [36][37][38] Oleuropein, tyrosol and hydroxytyrosol, the most abundant polyphenols in olive oil, have been related to several beneficial effects on bone metabolism in vitro an in animal models. [39] In humans, osteopenic subjects who consumed 250 mg/day of a polyphenol extract from Olea europaea for 12 months significantly increased their osteocalcin levels and stabilized lumbar spine BMD compared to a control group.…”
mentioning
confidence: 99%
“…The molecule potentially has wide-ranging pharmacological effects on cardiac 9) , inflammatory 10) , oncological 11) , and psychiatric diseases 12) . Thus, this polyphenol is thought to be a promising substance with applicability as a drug in nutritional supplements and biomaterials 8,[13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…For EGCG, various techniques have been developed to retain or deliver EGCG in the affected areas; these techniques include chemical bonding to polymers 14,16,18) , layer by layer technique 19) , hydrophobic and/or hydrogen bonding 20,21) , EGCG-coating associated with Na + -mediated physical self-assembly 22) and oxidative polymerization 3) , and en-capsulation in drug carriers 23) . Although our understanding of the application of this molecule in bone regenerative therapy remains limited when compared with that in other medical fields, we previously found that gelatin sponges chemically modified with EGCG using an aqueous chemical synthesis method (hereafter designated as AC-EGCG-GS) induced superior bone formation in critical-sized bone defects (4.2 mm of diameter) in mouse calvaria 14) . More recently, we showed that the bone-forming ability of vacuum-heated AC-EGCG-GS (AC-vhEGCG-GS) was greater than that of vacuum-heated gelatin sponges (without EGCG) in critical-sized bone defects (9 mm of diameter) of rat calvaria 18) .…”
Section: Introductionmentioning
confidence: 99%